Applying OECD policy evaluation criteria to child protection schemes in India - Lekha Chakraborty; Jitesh Yadav; Balamuraly B; Amandeep Kaur (Levy Economics Institute of Bard College, 2023)
The policy evaluation is a crucial component in analyzing the efficacy of public spending in translating the money spent into desired outcomes. Using OECD evaluation criteria, we analyzed the child protection schemes of Odisha to understand whether legal commitments on child protection are translated into fiscal commitments. The intergovernmental fiscal transfers and state-targeted programs for children in need of care and protection (CNCP) and children in conflict of law (CCL) are evaluated using the OECD criteria of relevance, coherence, effectiveness, efficiency, and sustainability. Using the theory of change, various fiscal interventions for child protection are analyzed with activities, outputs, intended outcomes, and impacts. The analysis revealed that, in the post-pandemic fiscal strategy of Odisha, various programs have been designed by the government to tackle the capability deprivation, hardships, and vulnerabilities faced by children within the budgetary frameworks, and that these programs are made fiscally sustainable through public expenditure convergence within the classification of budgetary transactions. However, the low utilization ratios of the funds and the institutional constraints are identified as challenges in the effective implementation of child protection programs in Odisha.
Keywords: D0; H5; H6; I3; J13; 330; Public Financial Management; OECD DAC Evaluation; Social Spending; Child Protection